Performance of Green Zinc Oxide Nanofluids in Membrane Photocatalytic Reactor: The Effect of Nanofluids Concentration - Idris, Muhammad Akmal Hisyam; Abu Bakar Sidik, Dilaeleyana; Noor Yahida Yahya (Journal of Science and Technology, 2026)
Recently, researchers exploring membrane photocatalytic reactor (MPR) treatment employing Zinc Oxide (ZnO) nanoPARticles incorporated capping agents due to their ability to boost photocatalytic performance and reduce fouling. The performance of ZnO–incorporated Pandanus amaryllifolius Roxb. nanofluids (ZnO–PAR) at varying concentrations for palm oil mill secondary effluent (POMSE) treatment via MPR was the main focus of this investigation. The maximum removal effectiveness of color (99.2%), total suspended solid (TSS) (93.6%), turbidity (95.6%), chemical oxygen demand (COD) (96.8%), permeate flux (23.9±0.3 L/m2.hr) and normalized flux (0.47) was achieved at 1.0 wt% ZnO–PAR nanofluids. According to this study, 1.0 wt% produced an ideal balanced and effective performance, demonstrating the substantial potential for use in the palm oil sector since it optimized flux and minimize membrane fouling. While the highest pollutant removal efficiencies were achieved at the lower concentrations (0.1 and 0.25 wt%). This green nanotechnology provides a viable tertiary treatment solution that meets environmental discharge limits outlined in Malaysia’s Environmental Quality Act 1974.